Clinical and Laboratory Biomarkers in the Management of Pancreatic Adenocarcinoma - Strimpakos, Alexios S; Syrigos, Kostas N; Saif, Muhammad W (JOP. Journal of the Pancreas, 2012)
Despite improvements in the health service and the available treatment means, the outcome of the majority of patients with advanced pancreatic adenocarcinoma, even in the Western world, is disappointing. This fact necessitates invention and development of clinical and laboratory biomarkers that help us detect early enough those patients who have the worst prognosis, and who may benefit or not from our treatments and individualize thus our management accordingly. In the 2012 American Society of Clinical Oncology (ASCO) Annual Meeting, four interesting scientific works on biomarkers in pancreatic cancer were presented. Two of them presented new clinical data such as the correlation of hand and foot skin reaction with the prognosis of patients treated with capecitabine based treatment (Abstract #4023), and the independent association of early presentation of venous thromboembolic events with poor survival (Abstract #4037). The other two significant abstracts focused on new potential predictive laboratory biomarkers, such as the association of the baseline levels of serum albumin to benefit from bevacizumab enriched treatment (Abstract #4039) and the likely correlation of high insulin growth factor 1 (IGF-1) tissue expression to better prognosis in patients treated with the IGF-1 receptor monoclonal antibody (mAb) MK-0646 (Abstract #4054).